Communication topology reconstruction method for multi-agent cooperative control in polymorphic networks - Ruyun ZHANG; Geyang XIAO; Qihe SHAN; Tao ZOU; Dan LI; Fei TENG (Tongxin xuebao)
As the task objectives and working environment become more and more complex and changeable, considering the limitations of the cooperative control of a single multi-agent system under the unilateralism communication network, a communication topology reconstruction method for multi-agent cooperative control in polymorphic networks was studied.Firstly, the multi-lateral distributed cooperative control framework was constructed based on multi-agent system in the polymorphic network environment.Secondly, a communication topology reconstruction method was proposed for multiple multi-agent systems with different functions after networking, and a distributed control protocol was designed to achieve multi-consensus.Finally, a simulation example was given to verify that the proposed method can complete the communication topology reconstruction of multi-agent cooperative control in polymorphic network.